Analisis Kebutuhan Pengembangan Media Puzzle Berbasis Pembelajaran Berdiferensiasi Pada Pembelajaran IPA Kelas V Sekolah Dasar - Dwi Ummu Aulia; Firmanul Catur Wibowo; Otib Satibi Hidayat (Jayapangus Press, 2026)
The implementation of the Kurikulum Merdeka (Independent Curriculum) encourages teachers to adopt differentiated instruction that accommodates the diverse characteristics of students. However, science instruction regarding food chains in elementary schools still faces a lack of learning media that supports differentiated instruction. This study aims to analyze the need for developing a differentiated-instruction-based puzzle medium for the food chain topic in Grade 5 elementary school, serving as the basis for formulating the medium's specifications. This study constitutes a preliminary study within the